Acute-on-chronic liver failure. Issue 10003 (17th October 2015) - Bernal, William; Jalan, Rajiv; Quaglia, Alberto; Simpson, Kenneth; Wendon, Julia; Burroughs, Andrew
Summary: Acute-on-chronic liver failure combines an acute deterioration in liver function in an individual with pre-existing chronic liver disease and hepatic and extrahepatic organ failures, and is associated with substantial short-term mortality. Common precipitants include bacterial and viral infections, alcoholic hepatitis, and surgery, but in more than 40% of patients, no precipitating event is identified. Systemic inflammation and susceptibility to infection are characteristic pathophysiological features. A new diagnostic score, the Chronic Liver Failure Consortium (CLIF-C) organ failure score, has been developed for classification and prognostic assessment of patients with acute-on-chronic liver failure. Disease can be reversed in many patients, and thus clinical management focuses upon the identification and treatment of the precipitant while providing multiorgan-supportive care that addresses the complex pattern of physiological disturbance in critically ill patients with liver disease. Liver transplantation is a highly effective intervention in some specific cases, but recipient identification, organ availability, timing of transplantation, and high resource use are barriers to more widespread application. Recognition of acute-on-chronic liver failure as a clinically and pathophysiologically distinct syndrome with defined diagnostic and prognostic criteria will help to encourage the development of new management pathways and interventions to address the unacceptably high mortality.